2004
DOI: 10.1246/cl.2004.1332
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted Synthesis of Flower-like ZnO Nanosheet Aggregates in a Room-temperature Ionic Liquid

Abstract: A fast and environment-friendly green microwave-heating route to synthesize flower-like ZnO nanosheet aggregates in a room-temperature ionic liquid has been reported. SEM images showed the nanosheets with uniform 50 nm in thickness. The PL spectrum of ZnO nanosheet aggregates exhibits a weak ultraviolet emission and a strong green emission at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Cao et al also reported the importance of using ionic liquids in combination with microwave heating to produce ZnO nanosheets, suggesting that this combination of method and solvent plays a critical role in formation of these structures. 182 Wang and Zhu showed that both ionic liquid and reaction temperature were important in controlling the morphology of Co 3 O 4 nanorods. 186 It is unclear why this combination is so effective, but its speed, the use of benign reactants, the ability to scale up product quantities, and the ultimate purity of the final product make this technique a potentially useful green application.…”
Section: Microwavementioning
confidence: 99%
“…Cao et al also reported the importance of using ionic liquids in combination with microwave heating to produce ZnO nanosheets, suggesting that this combination of method and solvent plays a critical role in formation of these structures. 182 Wang and Zhu showed that both ionic liquid and reaction temperature were important in controlling the morphology of Co 3 O 4 nanorods. 186 It is unclear why this combination is so effective, but its speed, the use of benign reactants, the ability to scale up product quantities, and the ultimate purity of the final product make this technique a potentially useful green application.…”
Section: Microwavementioning
confidence: 99%
“…[240,241] Although the synthesis of metal oxides in ionic liquids or mixed solutions containing ionic liquids has just begun, the number of publications in this direction is much more than that on the synthesis of silicas using ionic liquids because of the diversity of metal oxides. Typical examples include the synthesis of TiO 2 , [47,48,[242][243][244][245][246][247][248][249][250][251][252][253][254][255] ZnO, [43,[256][257][258][259][260][261][262][263][264][265][266] CuO, [267][268][269][270][271] Cu 2 O, [272] Fe 2 O 3 , [273,274] NiO, [275] ZrO 2 , [276] Co 3 O 4 , [277,278] CeO 2 , [279,280] SnO 2 , [281,282] PbO, …”
Section: Metal Oxidesmentioning
confidence: 99%
“…[ OHMim] þ ¼ 1-(2-hydroxyethyl)-3-methylimidazolium), [257] [BMim][Cl], [258] and [BMim] [BF 4 ]. [258] Interestingly, Xie and co-workers fabricated hexagonal micropyramids of ZnO using a mixture of oleic acid and ethylenediamine as the solvent (Fig.…”
Section: Metal Oxidesmentioning
confidence: 99%
“…Nanorods and nanowires were made out of Co 3 O 4 , 55 Te, 184 and metal sulfides 165 using RTILs and microwave heating, whereas ZnO formed flower-like nanosheets. 182 Other solvents were employed in an attempt to produce Te nanorods and nanowires. Of the solvents tested, ILs were the most successful for formation of Te nanorods and nanowires.…”
Section: Microwavementioning
confidence: 99%